Determinação de resíduos de agrotóxicos em feijão preto empregando método QuEChERS e UHPLC-MS/MS - Larentis, Karina Ues (2023)
Brazil is the third largest producer of black beans (Phaseolus vulgaris L.) in the world, with 60% of its population consuming this legume. During bean cultivation, pesticides can be used at any stage of development and in any part of the plant. However, due to their adverse effects on human health, there are growing concerns about the risks associated with residual exposure to these substances in foods. Consequently, many countries have established maximum residue limits (MRLs) for pesticides in food. Analytical monitoring is often performed to determine if residues are present, targeting food safety, regulation, product liability, quality, research and/or proposed food labeling. The objective of this work was to evaluate the simple and rapid multi-residue method for the determination of 85 pesticides in black beans using ultra-performance liquid chromatography coupled to tandem mass spectrometry (UHPLCMS/MS).The extraction step was optimized testing the unbuffered (original) and buffered (acetate and citrate) versions of QuEChERS method. The final extraction step was performed with 10 g of sample (slurry) and 10 mL of acetonitrile, with the addition of the citrate QuEChERS salts. The performance of different sorbents for the cleanup step were evaluated, such as C18, secondary primary amine (PSA) and graphite carbon black (GCB). The pesticide residue analysis was performed with Acquity UPLCTM liquid chromatography coupled to a Xevo TQ MS/MS triple quadrupole mass spectrometer (Waters Corporation, USA) with positive and negative electrospray ionization interface in multiple selected reaction monitoring (SRM) mode. The chromatographic separation was performed using an BEH C18 column (50 mm x 2.1 mm, 1.7 µm particle size). The mobile phase used consisted of (A) water:methanol (98:2, v/v) and (B) methanol:water (98:2, v/v), both containing 5 mmol L-1 of ammonium formate and formic acid 0.1% (v/v), with a constant at flow rate of 0.225 mL min-1 . The injection volume was 10 μL and total run time was 10 min. The results of the accuracy and precision tests, evaluated at levels of 10, 25 and 50 e 100µg kg-1 (n = 6), proved to be adequate, since they showed recoveries between 70 and 120%, with RSD ≤ 20% for 85 compounds. The method LOQs were between 10 and 50 µg kg-1 The results suggest that the developed method is suitable for the regulatory-purpose analyses of pesticides in black beans.